Working atmosphere, job satisfaction and individual characteristics of community mental health professionals in integrated care - Götz, Katja (Health and social care in the community, 2018)
Working requirements of community mental healthcare professionals in integrated care are complex. There is a lack of research concerning the relation of job satisfaction, working atmosphere and individual characteristics. For the current study, a survey evaluating job satisfaction and working atmosphere of mental healthcare professionals in integrated care was performed. About 321 community mental healthcare professionals were included in the survey; the response rate was 59.5%. The professional background of community mental healthcare professionals included nursing, social work and psychology. Community mental healthcare professionals reported the highest satisfaction with colleagues and the lowest satisfaction with income. Moreover, it could be shown that more responsibility, more recognition and more variety in job tasks lead to an increase of overall job satisfaction. Healthcare for mentally ill patients in the community setting is complex and requires well-structured care with appropriate responsibilities within the team. A co-operative relationship among colleagues as well as clearly defined responsibilities seem to be the key for the job satisfaction of community mental healthcare professionals in integrated care.
First published: 05 September 2017
Gesehen am 14.09.2018